Rockfill Dam with Reinforced Concrete Watertight Diaphragm: Static and Dynamic Analysis of Stress and Deformations - Toderas , Mihaela (Advances and Challenges in Science and Technology Vol. 3, 2023)
This study presents the stress-strain state in the dam body depending on the type of rockfill that was performed according to the moment of completion of the dam and the first filling with water. Large dams are a very relevant instance for assessing seismic risk. On the one hand, the dams themselves are valuable, with ramifications for the entire economy via energy generation, water delivery systems for irrigation, flood protection, and so on. On the other side, dam structural deterioration can create severe disasters and expose the people to the consequences of abrupt floods. The situation in Romania is such that the future safety of existing dams should be considered. The first reason is because these dams were conceived and built on the basis of technical norms, the majority of which are no longer in effect; the second reason is the recent dramatic climate changes, which have resulted in an accumulation of water in progressively huge lakes. A third reasonable argument is the length of existing dams. The stress-deformation condition that occurs in the Rastolita dam body depending on the kind of rockfill is investigated in this research. Calculations were done for two cases, namely the completion of construction and the first filling of the dam with water. The results show that after completion of construction, the maximum settlement is recorded in the central area of the dam, below the middle third; horizontal displacements of the downstream prism are significantly higher compared to deformations of the upstream prism in the area where the used material has a higher compressibility. Maximum principal normal stress registers some local distortions within acceptable limits; minimum principal normal stress exhibits significant gradients in the first stage contact zone downstream of the dam slope with the tuff-pyroclastic embankment layer, as well as the first three layers of intercalated filling disposed near the slope. Stress increases caused by hydrostatic pressure after the initial filling do not result in stress concentrations in zones different than those recorded at construction completion.